Assessing the impact of neurosurgery and neuroanatomy simulation using 3D non-cadaveric models amongst selected African medical students - Berjo Dongmo Takoutsing; Berjo Dongmo Takoutsing; Ubraine Njineck Wunde; Ubraine Njineck Wunde; Yvan Zolo; Yvan Zolo; Geneviève Endalle; Geneviève Endalle; Geneviève Endalle; Dieunedort Arnold Menga Djaowé; Dieunedort Arnold Menga Djaowé; Léopoldine Sybile Ngoune Tatsadjieu; et al. (Frontiers in Medical Technology, 2023)
BackgroundLaboratory dissections are essential to acquire practical skills to perform neurosurgical procedures. Despite being traditionally done on cadavers, they are often unavailable and suffer from cultural barriers in the African context. Non-cadaveric UpSurgeOn neurosurgery models have been developed to bridge this barrier, providing an almost similar experience with the human body. This study aimed to assess the impact of the UpSurgeOn hands-on-touch non-cadaver model training amongst selected Cameroon medical students.MethodsAn anonymous 35-item questionnaire was distributed online using Google drive systems to medical students who attended UpSurgeOn's hands-on-touch non-cadaver model training course. These questions aimed to capture data on previous experience with neuroanatomy and neurosurgery practicals and the perception, attitudes, and impact of the UpSurgeOn neurosurgery tool.ResultsEighty-six students completed the survey. The mean age was 21.2 ± 1.868 years, 61.6% were males with 62.8% of respondents being medical students in preclinical years. Before the training, 29.4% had a fair knowledge of neuroanatomy. Textbooks and Youtube videos were the main sources of neuroanatomy and neurosurgery knowledge for more than half of the respondents. Up to 91.5% had no prior exposure to a neuroanatomy/neurosurgery cadaver laboratory dissection, and 22.6% and 17.6% had witnessed and performed at least one craniotomy before, respectively. There were 11.1%, 15.5%, and 31.3% of our respondents who had used a surgical microscope, a neurosurgical instrument, and the UpSurgeOn Neurosurgery tool before, respectively. The majority perceived the UpSurgeOn tool easy to use and felt they needed to learn just a few things before getting going with the box. Most thought of increasing the use of the UpSurgeOn Box and saw the need to be part of the training curriculum. Finally, the majority felt this tool helped to increase familiarity and acquire neurosurgical skills, and to develop the orientation skills needed during neurosurgical approaches.ConclusionUndergraduate exposure to traditional neurosurgery/neuroanatomy labs is limited in Cameroon. Neurosurgery/neuroanatomy practical skills are gained essentially using non-practical means. Most students found the UpSurgeOn tool user-friendly, saw the need to incorporate it as part of their training, and perceived it to be essential in getting acquainted with neurosurgical skills.